2021
DOI: 10.1017/s0140525x20001375
|View full text |Cite
|
Sign up to set email alerts
|

Sex and drugs and rock and roll

Abstract: This article is extraordinarily rigorous and rich, although there are reasons to be skeptical of its theory that music originated to signal group quality and infant solicitude. These include the lack of any signature of the centrality of these functions in the distribution or experience of music; of a role for the pleasure taken in music; and of its connections with language.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 987 publications
0
7
0
Order By: Relevance
“…Steven Pinker made this famous statement about music: "I suspect that music is auditory cheesecake, an exquisite confection crafted to tickle the sensitive spots of at least six of our mental faculties" (Pinker, 1997, p. 534). The faculties to which he was referring were language, represented in the form of song lyrics, auditory scene analysis involving the detection of the sources of sounds, emotional calls as music can sometimes sound similar to wailing or moaning, habitat selection involving identifying sounds that indicate a safe or unsafe environment, and motor control needed for tasks such as walking and running (Pinker, 1997). Recent research supports the byproduct (or auditory cheesecake) hypothesis, as one study revealed that musician status did not predict preferences for prospective mates.…”
Section: Cognitive Byproductmentioning
confidence: 99%
See 1 more Smart Citation
“…Steven Pinker made this famous statement about music: "I suspect that music is auditory cheesecake, an exquisite confection crafted to tickle the sensitive spots of at least six of our mental faculties" (Pinker, 1997, p. 534). The faculties to which he was referring were language, represented in the form of song lyrics, auditory scene analysis involving the detection of the sources of sounds, emotional calls as music can sometimes sound similar to wailing or moaning, habitat selection involving identifying sounds that indicate a safe or unsafe environment, and motor control needed for tasks such as walking and running (Pinker, 1997). Recent research supports the byproduct (or auditory cheesecake) hypothesis, as one study revealed that musician status did not predict preferences for prospective mates.…”
Section: Cognitive Byproductmentioning
confidence: 99%
“…The cultural courtship model does not explain all cultural displays, and the status competition model has not been well tested. Another perspective on cultural displays (including music) suggests that they serve no function and instead are a byproduct of high intelligence in humans or the general ability to adopt culture (Hodgson & Verpooten, 2015; Lieberman & Billingsley, 2021; Pinker, 2021). Steven Pinker made this famous statement about music: “I suspect that music is auditory cheesecake, an exquisite confection crafted to tickle the sensitive spots of at least six of our mental faculties” (Pinker, 1997, p. 534).…”
Section: Mate Attractionmentioning
confidence: 99%
“…The evolution of music and musicality, which Honing (2018) defined as the biological capabilities that enable the creation and consumption of music, have long been topics for debate. Pinker's (1997) offhand determination that music was "auditory cheesecake," which was emblematic of a general hypothesis that music is a nonadaptive by-product of other evolved capacities, may have brought the debate, which had long occupied music scholars, to the scientific and popular mainstream and provoked several responses. Cross (2001) argued that music was crucial to the evolution of the human mind and that it is particularly relevant to humankind's success as a social, communal species and the emergence of culture (Cross, 2008).…”
Section: Competing Theories Of Musical Evolutionmentioning
confidence: 99%
“…Much of this discussion has revolved around music's status as an adaptation-an innate capacity that serves a specific, naturally selectable purpose-an exaptation-a technology or by-product of adaptations-or something akin to what Huron (2001) called "non-adaptive pleasure seeking" or Patel (2010Patel ( , 2018 described as a "transformative technology of the mind." The culture-cognition-mediator model, at first glance, appears to be something of an enigma because it views music through a constructionist lens that closely resembles Pinker's nonadaptationist view (Pinker, 1997) but gives music the precise functionality that Cross and others have argued was adaptive (Cross, 2001(Cross, , 2003(Cross, , 2008Honing, 2018;Killin, 2016).…”
Section: Ontological Implicationsmentioning
confidence: 99%
See 1 more Smart Citation